2020
DOI: 10.1007/s10699-020-09706-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Stigmatisation: Results of a Qualitative Formative Study with Adolescents and Adults in DR Congo

Abstract: While stigmatisation is universal, stigma research in low- and middle-income countries (LMIC) is limited. LMIC stigma research predominantly concerns health-related stigma, primarily regarding HIV/AIDS or mental illness from an adult perspective. While there are commonalities in stigmatisation, there are also contextual differences. The aim of this study in DR Congo (DRC), as a formative part in the development of a common stigma reduction intervention, was to gain insight into the commonalities and difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…effective [2,27,48] and; (v) be implementable by non-specialists to increase its usability [54,55]. The conclusions on cross-stigma applicability and the need for a socio-ecological response were confirmed by qualitative research carried out in DR Congo, which additionally highlighted the need for a simplified contexualisation tool [43].…”
Section: Plos Onementioning
confidence: 84%
See 2 more Smart Citations
“…effective [2,27,48] and; (v) be implementable by non-specialists to increase its usability [54,55]. The conclusions on cross-stigma applicability and the need for a socio-ecological response were confirmed by qualitative research carried out in DR Congo, which additionally highlighted the need for a simplified contexualisation tool [43].…”
Section: Plos Onementioning
confidence: 84%
“…This intervention intended to (i) have children and adolescents both as target and impact group; (ii) be applicable across stigmas, increasing its relevance as set out in recent research that advocates for moving away from stigma-siloed approaches [ 48 , 50 ]; (iii) apply a combination of promising and often-used stigma reduction ingredients such as social contact [ 25 ], knowledge and awareness raising [ 51 ], popular opinion leaders [ 52 ] and empowerment of PWLE [ 53 ]; (iv) address stigma at multiple levels within the community–from targeting PWLE to strengthen their stigma resistance and coping to the community at large—to be most effective [ 2 , 27 , 48 ] and; (v) be implementable by non-specialists to increase its usability [ 54 , 55 ]. The conclusions on cross-stigma applicability and the need for a socio-ecological response were confirmed by qualitative research carried out in DR Congo, which additionally highlighted the need for a simplified contexualisation tool [ 43 ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Single motherhood due to premarital childbirth may also result in negative community perceptions and stigma. A recent study conducted in the DRC suggested that there was a degree of stigma toward both adolescent and unmarried adult mothers For instance, community members expressed a fear of losing social status or being disliked if they associated with single mothers, perceiving out-of-wedlock childbirth to be immoral and regarding single mothers as having a low value and contribution to society [ 14 ].…”
Section: Introductionmentioning
confidence: 99%